PERKEMBANGAN PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM PROSES AUDIT: SEBUAH TINJAUAN LITERATUR KONTEMPORER - Hidayatullah, Rahmat; Nasruddin, Nasruddin; Syamsuddin, Syamsuddin; Arifuddin, Arifuddin (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
The development of digital technology has driven significant transformation in audit practices, especially through the use of Artificial Intelligence (AI). This study aims to present a literature review of the trends in the implementation of AI in auditing, the challenges faced, and its implications for the auditor profession in the 2018–2024 period. The method used was a review of the narrative literature conducted through article search on Google Scholar, ScienceDirect, and DOAJ databases using keywords related to audit and AI. A total of 10 articles were selected based on criteria: published in scientific journals, focused on AI in auditing, and relevant to improving audit quality. The results of the study show that AI plays an important role in increasing the effectiveness of risk assessment (with an accuracy of up to 90%), real-time anomaly detection, and the efficiency of audit procedures through process automation. Conclusion: AI serves as an augmentation tool that reinforces the professionalism of auditors, not as a substitute for the role of human auditors. However, challenges such as uneven auditor competence, algorithm transparency, data security, and the absence of AI-based auditing standards are still crucial issues. Thus, it is necessary to strengthen auditor digital literacy, develop a regulatory framework related to digital audit evidence, and further research on technology governance in auditing.